G-Jitter Effects On The Mixed Convection Flow Of Nanofluid Past An Inclined Stretching Sheet - Noraihan Afiqah, Rawi; Abdul Rahman, Mohd Kasim; Zaiton, Mat Isa; Aurangzaib, Mangi; Sharidan, Shafie (Global Digital Central, 2017)
Mixed convection flows of nanofluid past an inclined stretching sheet with g-jitter is studied in this paper. Water based nanofluid containing copper, copper oxide, aluminium oxide and silver nanoparticles are concerned. Coupled nonlinear partial differential equations are solved numerically using an implicit finite difference scheme. The effect of solid nanoparticles volume fraction parameter, amplitude of modulation, frequency of oscillation, mixed convection and inclination angle parameter on the fluid flow and heat transfer characteristics are graphically presented. The reduced skin friction and heat transfer coefficient are decreased when inclination angle and solid nanoparticles volume fraction parameters are increased.